PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI - B51110023, Wenny (Jurnal KIAFE, 2014)
This research aims to know the influence of corporate social responsibility disclosure on the company's profitability of basic industry and chemical sectors listed on the stock exchange. Proftabilitas ratio used is return on investment ratio, return on equity ratio, and gross profit margin ratio. Collecting data using purposive sampling method of basic industry and chemical sectors listed on the stock exchange in 2010 until 2012. A total of 11 companies qualified as research samples. Methods of data analysis using simple regression analysis. The results of this research indicate that the independent variables, namely the CSR disclosure positive and significant effect on the ratio of ROI, ROE, and GPM of the company. Keywords: Corporate Social Responsibility, Profitability, ROI, ROE, GPM.